2022
DOI: 10.1038/s41522-022-00287-y
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome responses to dietary intervention with hypocholesterolemic vegetable oils

Abstract: Hypercholesterolemia is becoming a problem with increasing significance. Dietary vegetable oils may help to improve this condition due to presence of phytonutrients with potentially synergistic cholesterol-lowering effects. The objective of this 8-week double-blinded randomized clinical trial was to investigate the effects of consuming 30 g of two different blended cooking oils, rich in omega-3 alpha-linolenic acid and phytonutrients, or refined olive oil on the intestinal microbiota in 126 volunteers with bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Since the estimate of the AGN from 16S rRNA data might be quite imprecise, we performed additional validation of partial correlation results using “shotgun” metagenomic dataset related to a dietary intervention 53 . The intervention included 126 subjects who consumed blended cooking oils or refined olive oil for 8 weeks (three time points were collected: baseline, 2 weeks and 8 weeks).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the estimate of the AGN from 16S rRNA data might be quite imprecise, we performed additional validation of partial correlation results using “shotgun” metagenomic dataset related to a dietary intervention 53 . The intervention included 126 subjects who consumed blended cooking oils or refined olive oil for 8 weeks (three time points were collected: baseline, 2 weeks and 8 weeks).…”
Section: Resultsmentioning
confidence: 99%
“…One “shotgun” metagenomic dataset 53 described microbiome changes during the intervention including intake of blended cooking oils or refined olive oil for 8 weeks ( N = 126 subjects, 3 time points); it was used for: validation of response associations with alpha diversity, AGN and B:F; validation of AGN calculation. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study on 126 participants with borderline hypercholesterolemia indicated that during the dietary intervention, the relative abundance of a single species, Clostridium leptum , increased dramatically, and along with that, various plasma markers of the metabolic health status improved, including apolipoprotein B, triglyceride, and the ratio of total cholesterol to HDL. In this study, butyrate production was discussed as a possible process for improving blood lipid profile [ 134 ].…”
Section: Influence Of Anti-inflammatory Diet On Gut Microbiota Insuli...mentioning
confidence: 99%